2013
DOI: 10.1016/j.jval.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Patient-Reported Outcome Instruments for Research to Support Medical Product Labeling: Report of the ISPOR PRO Good Research Practices for the Assessment of Children and Adolescents Task Force

Abstract: Additional research is needed to provide methodological guidance for future studies, especially for studies involving young children and parents' observational reports. As PRO data are increasingly used to support pediatric labeling claims, there will be more information regarding the standards by which these instruments will be judged. The use of PRO instruments in clinical trials and regulatory submissions will help ensure that children's experience of disease and treatment are accurately represented and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
462
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(511 citation statements)
references
References 130 publications
(200 reference statements)
12
462
0
6
Order By: Relevance
“…The latter are therefore the method of choice in clinical trials (Walterfang et al 2013). Since the concept of HrQoL is based on subjective experience, self-assessment using ageappropriate instruments is the gold standard (Matza et al 2013). Self and proxy reports are not interchangeable (Upton et al 2008), but proxy reports are valuable in very young or cognitively impaired patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter are therefore the method of choice in clinical trials (Walterfang et al 2013). Since the concept of HrQoL is based on subjective experience, self-assessment using ageappropriate instruments is the gold standard (Matza et al 2013). Self and proxy reports are not interchangeable (Upton et al 2008), but proxy reports are valuable in very young or cognitively impaired patients.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, patients and parents are involved as "content experts" (Matza et al 2004). Focus group interviews are the method of choice to identify topics, concerns and resources relevant in everyday life (Matza et al 2013). This paper presents the qualitative content analysis of focus group and single interviews with IT-IEM patients and their parents.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings informed modifications to every SCIM-III SR item and response scale, producing a pediatric version of the tool that we 18 assuming that the items and response scales are written with clarity, simplicity and minimal cognitive burden. 19 We previously showed that youths with SCI as young as age 8 were able to understand and respond to questions. 13 A fundamental problem with the SCIM-III SR was that youths did not understand the majority of the words and phrases.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging children to evaluate reading and comprehension of items on patient reported outcome instruments, as has been done in this study, is essential prior to using them in research or practice. 19 Two other problems encountered by children when reading and responding to the SCIM-III SR were vagueness of terminology and unfamiliarity with medical jargon. Even though the youths in this study had been injured for approximately 4½ years, they were unfamiliar with the meaning of the medical words in the SCIM-III SR. As a way to eliminate medical jargon and provide clarity, preambles enabled children to understand and appropriately respond to items that asked about complex health situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation